Cruelty against domestic animals: a comparative study between Malaysia and Alabama, United States of America / Siti Noorshaznee Tajuddin, Hazwanie Husain Bustari and Mazliza Abd Wahid - Tajuddin, Siti Noorshaznee; Husain Bustari, Hazwanie; Abd Wahid, Mazliza (2007)
This research aims to examine the efficiency of relevant laws with regards to cruelty to animals in Malaysia. This research will also make comparative studies between Malaysia and Alabama, United States of America. The main act which governs cruelty to animals in Malaysia is the Animal Act 1953 and as for Alabama, the governing act would be Alabama Consolidated Cruelty Statutes and Consolidated Dog Laws. Despite the amendments that have been made to the Animal Act 1953, there were no changes made to the relevant section regarding the punishments for the offenders of cruelty against animals. Due to the existence of only one act in governing this matter, there is lack of effectiveness in terms of the punishments which have been thoroughly discussed in this research.